Comprehensive evaluation of the psychosocial parameters of epilepsy: A representative population‐based study in Prey Veng (Cambodia). Issue 8 (11th May 2013) - Bhalla, Devender; Chea, Kimly; Chamroeun, Hun; Vichea, Chan; Huc, Pierre; Samleng, Chan; Sebbag, Robert; Gérard, Daniel; Dumas, Michel; Oum, Sophal; Druet‐Cabanac, Michel; Preux, Pierre‐Marie
Abstract Purpose We conducted a population‐based study of epilepsy in Prey Veng (Cambodia) to explore self‐esteem, fear, discrimination, knowledge–attitude–practice (KAP), social‐support, stigma, coping strategies, seizure‐provoking factors, and patient‐derived factors associated with quality of life (QOL). Methods The results are based on a cohort of 96 cases and matched controls (n = 192), randomly selected from the same source population. Various questionnaires were developed and validated for internal consistency (by split‐half, Spearman‐Brown prophecy, Kuder‐Richardson 20), content clarity and soundness. Summary, descriptive statistics, classical tests of hypothesis were conducted. Uncorrected chi‐square was used. Group comparison was done to determine statistically significant factors, for each domain, by conducting logistic regression; 95% confidence interval (CI) with 5% (two‐sided) statistical significance was used. Key Findings All questionnaires had high internal consistency. Stress was relevant in 14.0% cases, concealment in 6.2%, denial in 8.3%, negative feelings in public in 3.0%. Mean self‐esteem was 7.5, range 0–8, related to seizure frequency. Mean discrimination was least during social interactions. Coping strategies were positive (e.g. look for treatment). Postictal headache, anger, no nearby health facility, etc. were associated with QOL. Significance The reliability of our questionnaires was high. A positive social environment was noted with many infrequent social and personal prejudices. Not all populations should (by default) be considered as stigmatized or equipped with poor KAP. We addressed themes that have been incompletely evaluated, and our approach could therefore become a model for other projects.